Physio-chemical properties, meat quality and consumer preferences of meat from Potchefstroom koekoek and Ovambo chicken - Motsepe, Ramokone Johanna (My University, 2016)
A total of 320 male and female day old Ovambo and Potchefstroom koekoek (PK) chickens, were randomly assigned to a 2 (breed) × 2 (sex) factorial arrangement in a completely randomised design. Meat quality traits of male and female Ovambo and Potchefstroom Koekoek chickens were evaluated in this comparative study. The chickens were raised from day-old and fed on a commercial grower diet with 11.5 MJ/ME kg DM and 20% crude protein. The carcass traits of the Ovambo and Potchefstroom Koekoek (PK) were similar (P>0.05) except for breast yield. Sex affected on all carcass traits. Breed, sex, and time interactions influenced colour parameters of thigh and drumstick meat except redness (a*) and yellowness (b*) values of chicken breast meat. The pH varied significantly (P<0.05) between the breeds, sex and time period. The sensory evaluations of the chicken breeds were similar (P>0.05). However, tenderness of the breast meat as measured by shear force was higher for PK than that of Ovambo chickens. Fatty acid profiles of the chickens were not affected (P>0.05) by breed or sex. The ratios of n-6 and n-3 fatty acids were significantly lower in both breeds which are desirable in reducing the risk of many heart-related diseases. The information obtained from this study can assist efforts to promote production of indigenous chickens. The information also sheds some light in terms of consumer awareness for healthier meat choices. Keywords: Breed, Carcass traits, Meat colour, meat pH, Fatty acids
Thesis (M.A. Agricultural Management (Animal Production)) -- University of Limpopo, 2016
Keywords: Meat quality; Indigenous chickens; Chicken breeding; Chickens -- Breeding; Poultry -- Breeding; Meat -- Quality